Electrode assembly, preparation method thereof and solid-state battery

By using electrode components including the first and second solid electrolytes in the lithium-ion battery, combining the substrate layer and the lithium-philic layer to build a negative electrode-free lithium battery, the problems of improving energy density, circulation performance and safety hazards of lithium-ion battery are solved. Higher energy density and cycling performance are achieved and the risk of thermal runaway is reduced.

CN119297197APending Publication Date: 2025-01-10JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411612568.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

There is room for improvement in the energy density and cycling performance of existing lithium-ion batteries, especially the safety and ion conductivity of all-solid-state negative electrode-free lithium batteries need to be improved.

Method used

An electrode assembly including a positive electrode sheet and a composite electrode sheet is adopted. The positive electrode sheet includes a first solid electrolyte. The composite electrode sheet is provided with a second solid electrolyte close to the positive electrode sheet. The voltage window of the second solid electrolyte is less than or equal to the first solid electrolyte, and the bonding base is The material layer and the lithium-philic layer form an electrode assembly without conventional negative electrode material coating, and are used to construct a negative electrode lithium battery.

Benefits of technology

It improves the energy density and cycling performance of the battery, reduces the weight of the electrode assembly, avoids the side reaction between lithium metal and electrolyte, enhances the safety and ionic conductivity of the battery, and reduces the risk of thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297197A_ABST
    Figure CN119297197A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to an electrode assembly, a preparation method thereof and a solid-state battery. The electrode assembly comprises a positive plate and a composite plate, the positive plate comprises an active material layer, and the active material layer comprises a first solid electrolyte; the composite pole piece comprises a solid electrolyte layer, the solid electrolyte layer is arranged close to the active material layer, the solid electrolyte layer comprises a second solid electrolyte, and the voltage window of the second solid electrolyte is smaller than or equal to the voltage window of the first solid electrolyte. The solid-state battery comprises the electrode assembly. The voltage window of the second solid electrolyte is limited to be smaller than or equal to the voltage window of the first solid electrolyte, so that the oxidation stability of the positive plate is improved, the voltage platform of the whole battery can be improved, the energy density of the battery is improved, and the weight of the battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to an electrode assembly and a preparation method thereof, and a solid-state battery. Background Art

[0002] Lithium-ion batteries have developed rapidly due to their advantages such as high operating voltage, high energy density, long cycle life, and no memory effect, and are widely used in various battery fields, such as electric vehicles, laptops, mobile phones, and mobile power supplies. However, the low specific capacity of the graphite negative electrode used in existing lithium-ion batteries limits the further improvement of its energy density. Therefore, the development of the next generation of new battery systems with higher energy density has become an urgent problem that needs to be solved. The metal lithium negative electrode can greatly improve the energy density of lithium batteries using it because of its extremely high theoretical specific capacity (about 3860mAh / g) and the lowest electrochemical potential (-3.04V relative to the standard hydrogen electrode). Furthermore, the negative electrode-free battery obtained by removing the metal lithium has the highest energy density that can be achieved by adjusting the negative electrode, which can further break through the energy density of the battery.

[0003] However, the existing anode-free lithium batteries still have some potential safety hazards in practical applications, especially in liquid organic electrolyte systems. By making the anode-free lithium batteries free of liquid electrolyte, that is, using all-solid-state anode-free lithium batteries, some safety hazards can be reduced or avoided. However, the existing all-solid-state anode-free lithium batteries still have certain shortcomings, such as their energy density or ion conductivity, which need to be further improved.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides an electrode assembly and a preparation method thereof and a solid-state battery, which can improve energy density, reduce the weight of the electrode assembly, and also help improve the cycle performance of the battery.

[0006] In order to solve the above technical problems, this application is implemented as follows: According to one aspect of the present application, an embodiment of the present application provides an electrode assembly, the electrode assembly comprising: a positive electrode sheet and a composite electrode sheet; The positive electrode sheet includes an active material layer, and the active material layer includes a first solid electrolyte; The composite pole piece includes a solid electrolyte layer, the solid electrolyte layer is arranged close to the active material layer, the solid electrolyte layer includes a second solid electrolyte, and the voltage window of the second solid electrolyte is less than or equal to the voltage window of the first solid electrolyte.

[0007] In addition, the electrode assembly according to the present application may also have the following additional technical features: In some embodiments, the first solid electrolyte includes at least one of a NASICON structure LATP electrolyte, a NASICON structure LAGP electrolyte, or a perovskite structure LLTO electrolyte.

[0008] In some embodiments, the second solid electrolyte includes at least one of a NASICON structure LATP electrolyte, a NASICON structure LAGP electrolyte, a perovskite structure LLTO electrolyte, a garnet structure LLZO electrolyte, a garnet structure LLZTO electrolyte, LiPON or LISICON.

[0009] In some of the embodiments, the composite pole piece further includes a substrate layer and a metal layer; The metal layer is disposed on at least one side surface of the substrate layer along the thickness direction; The solid electrolyte layer is disposed on a surface of the metal layer away from the substrate layer; Wherein, the material of the metal layer includes a metal material having lithium affinity.

[0010] In some embodiments, the metal material having lithium affinity includes at least one of gold, silver, tin, magnesium, antimony, indium or aluminum.

[0011] In some embodiments, the material of the substrate layer includes a polymer material; the polymer material includes at least one of polyamide, polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyterephthalamide, paraphenylenediamine, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber or polycarbonate.

[0012] In some of the embodiments, the composite electrode further comprises a substrate layer, a metal layer and a lithium-philic layer; The metal layer is disposed on at least one side surface of the substrate layer along the thickness direction; The lithium-philic layer is disposed on a surface of the metal layer away from the substrate layer; The solid electrolyte layer is disposed on a surface of the lithium-philic layer away from the metal layer.

[0013] In some embodiments, the material of the metal layer includes at least one of copper, nickel, titanium, chromium, steel, molybdenum or tungsten.

[0014] In some embodiments, the material of the lithium-philic layer includes at least one of tin oxide, copper oxide, zinc oxide, cobalt oxide, nickel oxide, cuprous sulfide or graphene.

[0015] In some embodiments, the material of the substrate layer includes a polymer material; the polymer material includes at least one of polyamide, polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyterephthalamide, paraphenylenediamine, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber or polycarbonate.

[0016] In some embodiments, the thickness of the lithium-philic layer is 1 μm to 5 μm.

[0017] In some embodiments, the substrate layer has a thickness of 3 μm to 20 μm.

[0018] In some embodiments, the thickness of the metal layer is 0.5 μm to 5 μm.

[0019] In some embodiments, the solid electrolyte layer has a thickness of 0.1 mm to 3 mm.

[0020] In some of the embodiments, the solid electrolyte layer further includes a binder.

[0021] In some embodiments, the positive electrode sheet further includes a current collector, and the active material layer is disposed on at least one side surface of the current collector along a thickness direction.

[0022] In some embodiments, the active material layer further includes a positive electrode active material, a conductive agent and a binder, and the mass ratio of the positive electrode active material, the first solid electrolyte, the conductive agent and the binder is (70-80): (15-28): (0-4): (0.5-2).

[0023] According to another aspect of the present application, an embodiment of the present application provides a method for preparing an electrode assembly, the method comprising: forming an active material layer on at least one side surface of the current collector to obtain a positive electrode sheet; forming a metal layer on at least one side of the substrate layer, and forming a solid electrolyte layer on the surface of the metal layer to obtain a composite electrode; Alternatively, a metal layer is formed on at least one side of the substrate layer, a lithium-philic layer is formed on the surface of the metal layer, and a solid electrolyte layer is formed on the surface of the lithium-philic layer to obtain a composite electrode; The positive electrode sheet and the composite electrode sheet are combined to obtain the electrode assembly.

[0024] According to another aspect of the present application, an embodiment of the present application provides a solid-state battery, which includes: the aforementioned electrode assembly or the electrode assembly prepared by the aforementioned preparation method.

[0025] Implementing the technical solution of the present invention has at least the following beneficial effects: (1) In the embodiments of the present application, the electrode assembly provided can be used to prepare a solid-state battery, and the positive electrode sheet and the composite electrode sheet in the electrode assembly can form a negative electrode-free lithium battery, wherein the composite electrode sheet can play the role of the negative electrode sheet and the isolation membrane in the negative electrode-free lithium battery, and the composite electrode sheet is not coated with conventional negative electrode materials, which can reduce the weight of the electrode assembly and help improve the energy density of the battery; in addition, the negative electrode-free lithium battery has no liquid electrolyte inside, which can avoid the problem of continuous side reactions between lithium metal and electrolyte, and can simultaneously improve the energy density and cycle performance of the battery.

[0026] (2) The positive electrode sheet in the provided electrode assembly includes an active material layer, the active material layer includes a first solid electrolyte, and a solid electrolyte layer is provided on the side of the composite electrode sheet close to the positive electrode sheet, so that lithium ions can be conducted in the positive electrode and the composite electrode sheet, which is beneficial to improve the ion conductivity. At the same time, by making the voltage window of the second solid electrolyte in the solid electrolyte layer less than or equal to the voltage window of the first solid electrolyte in the active material layer, the lithium potential (vs. Li / Li) of the first solid electrolyte in the active material layer is utilized. + ) is relatively high, which can improve the oxidation stability of the positive electrode. At the same time, the lithium potential of the solid electrolyte layer on the composite electrode side is ≤ the lithium potential of the first solid electrolyte in the positive electrode. In this way, the combination of the two has a high voltage platform for the entire battery, which can correspondingly improve the energy density of the battery and has a higher ionic conductivity.

[0027] (3) In some preferred embodiments of the present invention, the composite pole piece in the electrode assembly uses a substrate layer to replace part of the metal, which greatly reduces the weight of the current collector and thus improves the energy density of the battery. In addition, when the battery is short-circuited, since the substrate layer is a polymer material, the polymer material melts after being heated, the current collector breaks, and the current is blocked, thereby effectively reducing the probability of thermal runaway of the battery. On the other hand, the battery composed of composite pole pieces does not have liquid electrolyte, is not easy to burn, and can also effectively reduce the probability of thermal runaway.

[0028] (4) In some preferred embodiments of the present invention, the composite electrode in the electrode assembly may also adopt a scheme combining a lithium-philic layer and a solid electrolyte layer, or a scheme combining a lithium-philic metal material and a solid electrolyte layer. In this way, the lithium-philic layer or the lithium-philic metal material can be used to induce uniform electrochemical deposition of lithium ions, thereby effectively inhibiting lithium dendrites and alleviating the lithium dendrite problem existing in existing negative electrode-free lithium batteries.

[0029] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Shown is a schematic diagram of a composite pole piece structure provided in Example 1 of the present invention.

[0031] Description of reference numerals: 1- substrate layer; 2-Metal layer; 3-lithiophilic layer; 4- Solid electrolyte layer. DETAILED DESCRIPTION

[0032] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range or the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0035] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0036] Generally speaking, a negative electrode-free battery refers to a battery without negative electrode active materials. By not using negative electrode active materials, the negative electrode-free battery can improve the energy density of the battery. The technical principle of a negative electrode-free battery is to deposit the lithium in the positive electrode on the negative electrode current collector through formation charging or during the first charging process of the battery. A negative electrode-free lithium battery is a type of negative electrode-free battery. Existing negative electrode-free lithium batteries still have some potential safety hazards in practical applications, especially in liquid organic electrolyte systems. These challenges mainly include the growth of lithium dendrites. Lithium dendrites not only react with the electrolyte to cause poor cycle stability, but also easily puncture the diaphragm, causing a short circuit in the battery and causing a safety accident, thus limiting its commercial application.

[0037] In the related art, the patent with publication number CN117936922A discloses a composite structure and its preparation method and application, which reserves metal lithium deposition space in the three-dimensional current collector and constructs a metal lithium deposition inducing material layer to achieve precise induction of metal lithium deposition behavior, and combines the construction of a conductive carbon layer and a solid electrolyte layer to solve the lithium dendrite problem and alleviate the volume effect of metal lithium deposition; it helps to improve the first efficiency, cycle performance and rate performance of the battery. However, the battery of this solution still has liquid electrolyte, which cannot completely solve the problem of continuous side reactions between lithium metal and liquid electrolyte, and the patent does not improve the safety performance of the battery such as thermal runaway. In addition, the energy density of the battery of this solution needs to be further improved.

[0038] In view of this, the present application provides an electrode assembly and a solid-state battery including the electrode assembly, wherein the composite electrode sheet in the electrode assembly can constitute a part of a negative electrode-free lithium battery, and the composite electrode sheet is not coated with conventional negative electrode materials, which can reduce the weight of the electrode assembly, and the negative electrode-free lithium battery has no liquid electrolyte inside, which can avoid the problem of continuous side reactions between lithium metal and electrolyte, and can simultaneously improve the energy density and cycle performance of the battery. The specific technical solution is described below.

[0039] In some embodiments, the present application provides an electrode assembly, the electrode assembly comprising: a positive electrode sheet and a composite electrode sheet; Wherein, the positive electrode sheet includes an active material layer, and the active material layer includes a first solid electrolyte; The composite pole piece includes a solid electrolyte layer, which is arranged close to the active material layer. The solid electrolyte layer includes a second solid electrolyte, and the voltage window of the second solid electrolyte is less than or equal to the voltage window of the first solid electrolyte.

[0040] In the embodiment of the present application, the electrode assembly includes a positive electrode sheet and a composite electrode sheet, and the positive electrode sheet and the composite electrode sheet can form an electrode assembly, such as forming an electrode assembly in a non-negative electrode lithium battery, and when the two form an electrode assembly, the active material layer in the positive electrode sheet and the solid electrolyte layer of the composite electrode sheet are arranged adjacent to each other. That is, the provided electrode assembly can be used as an electrode assembly of a non-negative electrode lithium battery, so that the non-negative electrode lithium battery containing it does not contain a conventional solid electrolyte membrane or isolation membrane, and the composite electrode sheet plays the role of the negative electrode sheet and isolation membrane of the non-negative electrode lithium battery, thereby realizing the construction of a practical non-negative electrode lithium battery, and further achieving high energy density and long cycle life and good safety effects.

[0041] In detail, firstly, the positive electrode sheet and the composite electrode sheet in the provided electrode assembly can form a non-negative electrode lithium battery, wherein the composite electrode sheet can play the role of the negative electrode sheet and the separator in the non-negative electrode lithium battery, and the composite electrode sheet is not coated with conventional negative electrode materials, which can reduce the weight of the electrode assembly and help improve the energy density of the battery; in addition, the non-negative electrode lithium battery has no liquid electrolyte inside, which can avoid the problem of continuous side reactions between lithium metal and electrolyte, and can simultaneously improve the energy density of the battery and the cycle performance of the battery. In other words, the battery containing the electrode assembly can effectively improve the energy density and reduce the weight of the electrode assembly by forming a non-negative electrode battery. Moreover, it can be free of diaphragms or solid electrolyte membranes, omitting the diaphragm structure in traditional batteries, thereby reducing the difficulty of assembling solid-state batteries and further improving the energy density. In addition, there is no liquid electrolyte inside the electrode assembly, which can avoid the problem of continuous side reactions between lithium metal and electrolyte, thereby improving the cycle performance of the battery. At the same time, since there is no liquid electrolyte, the electrolyte will not flow during actual application, which can improve the battery's puncture safety. Therefore, by eliminating the liquid electrolyte in the battery, the battery's cycle performance (effectively alleviating the lithium dendrite problem) and safety performance (such as puncture safety issues) can be effectively improved.

[0042] Second, in the electrode assembly of the embodiment of the present application, the active material layer in the positive electrode sheet includes a first solid electrolyte, and the first solid electrolyte used includes a solid electrolyte material with a wide electrochemical window. The wide electrochemical window here refers to the selection of a high voltage material, and the material has a lithium potential (vs. Li / Li +) is high. As an example, the voltage window range of the first solid electrolyte can be 0 to 6V. Furthermore, the solid electrolyte layer in the composite electrode is arranged close to the active material layer of the positive electrode, and the junction of the two layers of solid electrolyte can enable lithium ions to conduct in the positive electrode and the composite electrode, which is beneficial to improve the ion conductivity. If there is no solid electrolyte in the positive electrode, an electrolyte needs to be added. Since the battery composed of composite electrodes has no liquid electrolyte, it is not easy to burn and can also effectively reduce the probability of thermal runaway.

[0043] It is particularly noteworthy that in the embodiment of the present application, the voltage window of the second solid electrolyte in the solid electrolyte layer is less than or equal to the voltage window of the first solid electrolyte, that is, the voltage window of the second solid electrolyte is ≤ the voltage window of the first solid electrolyte. By using solid electrolytes with different voltage windows, and the voltage window of the second solid electrolyte is ≤ the voltage window of the first solid electrolyte, the lithium potential (vs. Li / Li) of the first solid electrolyte in the positive electrode sheet is + ) is relatively high, which can improve the oxidation stability of the positive electrode sheet and can provide good protection for the positive electrode material under high voltage conditions. At the same time, the lithium potential of the second solid electrolyte in the solid electrolyte layer on the composite electrode side is ≤ the lithium potential of the first solid electrolyte in the positive electrode sheet. In this way, the combination of the two has a high voltage platform for the entire battery, which can correspondingly improve the energy density of the battery and has a higher ionic conductivity.

[0044] Therefore, based on the above, the present application forms an electrode assembly of a non-negative-electrode lithium battery through a positive electrode sheet and a composite electrode sheet, and the composite electrode sheet is not coated with conventional negative electrode materials, which can reduce the weight of the electrode assembly and improve the energy density. At the same time, by setting a first solid electrolyte in the positive electrode sheet and a solid electrolyte (i.e., a second solid electrolyte) in the composite electrode sheet, it is possible to eliminate the liquid electrolyte inside the non-negative-electrode lithium battery, avoid the problem of continuous side reactions between lithium metal and electrolyte, and simultaneously improve the energy density and cycle performance of the battery; it can also enable lithium ions to be conducted in the positive electrode sheet and the composite electrode sheet, which is beneficial to improving the ion conductivity. Moreover, it is further limited that the voltage window of the second solid electrolyte is less than or equal to the voltage window of the first solid electrolyte, which can improve the oxidation stability of the positive electrode sheet while also improving the voltage platform of the entire battery, thereby improving the energy density of the battery, and having a higher ion conductivity.

[0045] It should be pointed out that the present application does not limit the specific range of the specific voltage window (electrochemical window) of the first solid electrolyte and the second solid electrolyte. As long as the voltage window of the second solid electrolyte is ≤ the voltage window of the first solid electrolyte, the battery can have a high voltage, a high energy density, and a high ionic conductivity, and it does not limit the purpose of the present application. The specific ranges or values ​​of the two can be selected according to the specific circumstances when the voltage window of the second solid electrolyte is ≤ the voltage window of the first solid electrolyte, and they are not listed one by one here.

[0046] It should also be pointed out that the voltage window (electrochemical window) of the material can be measured by methods known in the art. For example, the electrochemical window can be tested by using the linear voltammetric test module of the electrochemical workstation. The material to be tested (the first solid electrolyte or the second solid electrolyte) and the binder are mixed in a certain mass ratio and drop-coated on the surface of the glassy carbon electrode as the working electrode. 1M LiPF 6 The solution is used, and the lithium sheet is used as the counter electrode to carry out voltammetric curve test with a voltage range of 2.5 to 5 V and a scan rate of 0.5 mV / s. The oxidation potential recorded is the electrochemical window.

[0047] It is understood that, when the voltage window of the second solid electrolyte is less than or equal to the voltage window of the first solid electrolyte, the specific types of the first solid electrolyte and the second solid electrolyte can be selected from any known electrolyte material. Optionally, the first solid electrolyte and the second solid electrolyte in the present application can be selected from the solid electrolyte materials listed below.

[0048] In some embodiments, the first solid electrolyte includes, but is not limited to, any one of a NASICON structure LATP electrolyte, a NASICON structure LAGP electrolyte, or a perovskite structure LLTO electrolyte, or a combination of at least two of them. Among them, the NASICON structure LATP electrolyte has the characteristics of safety, environmental stability, low cost, and a wide electrochemical window; the NASICON structure LAGP electrolyte has a more stable structure and relatively excellent performance; the perovskite structure LLTO electrolyte has high grain conductivity and good chemical stability.

[0049] In the embodiment of the present application, the first solid electrolyte in the positive electrode sheet is selected from a material having a relatively wide electrochemical window, such as a sodium superion conductor NASICON structure, such as LATP, a perovskite structure, such as LLTO, etc. By selecting the above solid electrolyte, the oxidation stability of the positive electrode sheet and the stability of the battery can be improved.

[0050] In some embodiments, the second solid electrolyte includes, but is not limited to, at least one of a NASICON structure LATP electrolyte, a NASICON structure LAGP electrolyte, a perovskite structure LLTO electrolyte, a garnet structure LLZO electrolyte, a garnet structure LLZTO electrolyte, LiPON or LISICON.

[0051] In the embodiment of the present application, the second solid electrolyte in the composite electrode piece is selected from a material that does not exceed the electrochemical window of the first solid electrolyte, such as LATP, a perovskite structure such as LLTO, a garnet structure such as LLZO, LLZTO, lithium phosphorus oxygen nitrogen LiPON, or a lithium superion conductor LISICON, etc. One or more. Through the selection of the above-mentioned second solid electrolyte, the voltage window of the first electrolyte in the positive electrode piece can be well adapted (the second solid electrolyte located in the composite electrode piece is less than or equal to the voltage window of the first solid electrolyte in the positive electrode piece, which can make the battery have a high voltage and obtain a high energy density), and has a high ionic conductivity.

[0052] In addition to the solid electrolyte layer in contact with the positive electrode, the composite electrode of the present application may also include a substrate layer for support, and a lithium-philic layer for further improving certain properties of the composite electrode, such as lithium-philicity. Moreover, the composite electrode of the present application may have several different structural forms.

[0053] As an example, in some embodiments, the composite pole piece further includes a substrate layer and a metal layer, that is, the composite pole piece includes a substrate layer, a metal layer and a solid electrolyte layer. The metal layer is arranged on at least one side surface of the substrate layer along the thickness direction; the solid electrolyte layer is arranged on the surface of the metal layer away from the substrate layer; the material of the metal layer includes a metal material with lithium affinity. That is, the composite pole piece includes a substrate layer, a metal layer and a solid electrolyte layer arranged in a stacked manner.

[0054] In the embodiment of the present application, the metal layer is disposed on at least one side surface of the substrate layer along the thickness direction. The above-mentioned "metal layer disposed on at least one side surface of the substrate layer along the thickness direction" means that the metal layer can be disposed on one surface of the substrate layer along its own thickness direction, or it can be disposed on two surfaces of the substrate layer along its own thickness direction. The "surface" here can be the entire area of ​​the substrate layer, or it can be a partial area of ​​the substrate layer. For example, in the present embodiment, the surface can be the entire area of ​​the substrate layer. The present application has no special restrictions on this, as long as the purpose of the present application can be achieved.

[0055] As an example, the substrate layer has two surfaces in its own thickness direction, and the metal layer is arranged on two opposite surfaces of the substrate layer. Further, a solid electrolyte layer is formed on the surface of the metal layer on both sides. It is understood that in other embodiments, the metal layer can also be stacked on any one of the two surfaces of the substrate layer.

[0056] In the embodiment of the present application, the solid electrolyte layer is disposed on the surface of the metal layer away from the substrate layer; the material of the metal layer includes a metal material having a lithium affinity. Optionally, the metal material having a lithium affinity includes, but is not limited to, any one of gold, silver, tin, magnesium, antimony, indium or aluminum, or a combination of at least two thereof.

[0057] By selecting the above-mentioned metal material with lithium affinity as the metal layer, on the one hand, the metal layer has a high electronic conductivity, plays a role in transmitting current, so that lithium ions can be deposited; on the other hand, the lithium affinity of the metal material can be used to induce uniform electrochemical deposition of lithium ions, which can effectively inhibit lithium dendrites and effectively alleviate the problem of lithium dendrites. Therefore, by setting the metal layer of the metal material with lithium affinity, it can play the role of metal conductivity, current transmission, etc., and can also play the role of having lithium affinity and being able to alleviate the problem of lithium dendrites.

[0058] In an embodiment of the present application, the material of the substrate layer includes a polymer material; optionally, the polymer material includes, but is not limited to, any one of polyamide, polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyterephthalamide, paraphenylenediamine, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber or polycarbonate, or a mixture of any proportion of at least two of them.

[0059] In the composite pole piece of the present invention, the substrate layer can play a partial supporting role through the provision of the substrate layer, and the present application uses a substrate layer of polymer material to replace part of the metal, which can greatly reduce the weight of the current collector and thus improve the energy density of the battery.

[0060] In addition, the substrate layer of the polymer material can play a role in suppressing thermal runaway. For example, when the battery is short-circuited, since the substrate layer of the composite pole piece is a polymer material, the substrate layer melts after heating, the current collector breaks, and the current is blocked, thereby effectively reducing the probability of thermal runaway of the battery. On the other hand, the battery composed of composite pole pieces has no liquid electrolyte, is not easy to burn, and can also effectively reduce the probability of thermal runaway.

[0061] In addition, in some other embodiments, the present application also provides another composite pole piece, which includes a substrate layer, a metal layer and a lithium-philic layer, that is, the composite pole piece includes a substrate layer, a metal layer, a lithium-philic layer and a solid electrolyte layer. Among them, the metal layer is arranged on at least one side surface of the substrate layer along the thickness direction; the lithium-philic layer is arranged on the surface of the metal layer away from the substrate layer; the solid electrolyte layer is arranged on the surface of the lithium-philic layer away from the metal layer. That is, the composite pole piece includes a substrate layer, a metal layer, a lithium-philic layer and a solid electrolyte layer arranged in a stacked manner.

[0062] In the embodiment of the present application, the metal layer is arranged on at least one side surface of the substrate layer along the thickness direction. The arrangement here is the same as the above content. Please refer to the above content for the specific arrangement, which will not be repeated here. In addition, unlike the arrangement of the metal layer in the composite pole piece in the above embodiment, the material of the metal layer in this embodiment is not limited, such as it can be an ordinary metal material without lithium affinity, or it can also be a metal material with lithium affinity.

[0063] The metal layer is arranged between the substrate layer and the lithium-philic layer, has a high electronic conductivity, plays a role in transferring current, and enables lithium ions to be deposited. Optionally, the material of the metal layer includes, but is not limited to, any one of copper, nickel, titanium, chromium, steel, molybdenum or tungsten or a combination of at least two. By selecting the above-mentioned metal materials, not only are the sources wide and the prices low, but also the metal materials have a high electronic conductivity, can play a role in transferring current, and enable lithium ions to be deposited.

[0064] In the embodiment of the present application, the lithium-philic layer is arranged on the surface of the metal layer away from the substrate layer, that is, the lithium-philic layer is arranged between the metal layer and the solid electrolyte layer. Optionally, the material of the lithium-philic layer includes any one of tin oxide, copper oxide, zinc oxide, cobalt oxide, nickel oxide, cuprous sulfide or graphene, or a combination of at least two of them. When the metal layer does not contain a lithium-philic metal material, an additional lithium-philic layer is provided, and the lithium-philic layer is combined with the second solid electrolyte to induce uniform electrochemical deposition of lithium ions, thereby effectively suppressing lithium dendrites.

[0065] Preferably, the material of the lithium-philic layer is selected from graphene. More preferably, graphene is reduced graphene oxide. The graphene layer has lithium-philicity, can induce uniform electrochemical deposition of lithium ions, and effectively inhibit lithium dendrites. Therefore, by combining a lithium-philic layer such as a graphene layer with the above-mentioned solid electrolyte layer, it is possible to induce uniform electrochemical deposition of lithium ions, effectively inhibit lithium dendrites, and effectively alleviate various safety problems caused by existing lithium dendrites.

[0066] In the embodiment of the present application, the solid electrolyte layer is disposed on the surface of the lithium-philic layer away from the metal layer. The solid electrolyte layer has the same composition as the solid electrolyte layer of the previous embodiment, which will not be described again.

[0067] In the embodiment of the present application, the material of the substrate layer includes a polymer material; the polymer material includes, but is not limited to, at least one of polyamide, polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyterephthalamide, p-phenylenediamine, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber or polycarbonate. The specific material and function of the substrate layer are the same as those of the substrate layer in the aforementioned embodiment, and will not be repeated here.

[0068] In the above-mentioned composite electrode, the thickness of the lithium-philic layer can be 1μm to 5μm; as an example, the thickness of the lithium-philic layer can be any point value among 1μm, 2μm, 3μm, 4μm, 5μm, or a range value between any two. By making the thickness of the lithium-philic layer within the above-mentioned range, the requirements of the battery for energy density can be met at the same time, and the composite electrode can also have a higher conductivity, and the occurrence of lithium dendrites can be effectively suppressed. If the thickness of the lithium-philic layer is too small, the conductivity is low and the inhibitory effect on lithium dendrites is weakened. If the thickness of the lithium-philic layer is too large, the energy density is affected.

[0069] In the two composite pole pieces provided above, that is, the composite pole piece including a substrate layer, a metal layer and a solid electrolyte layer, and the composite pole piece including a substrate layer, a metal layer, a lithium-philic layer and a solid electrolyte layer, the thickness of the substrate layer can be the same. For example, the thickness of the substrate layer is 3μm to 20μm; as an example, the thickness of the substrate layer can be any point value of 3μm, 4μm, 6μm, 10μm, 11μm, 13μm, 20μm or a range value between any two. By making the thickness of the substrate layer within this range, certain strength requirements can be met, which is conducive to reducing energy density and playing a role in suppressing thermal runaway. If the thickness of the substrate layer is too small and the mechanical strength is low, the supporting strength may be weakened, or the role of reducing energy density may be weakened; if the thickness of the substrate layer is too thick, it may affect other electrical properties of the composite pole piece.

[0070] In the two composite pole pieces provided above, that is, the composite pole piece including a substrate layer, a metal layer and a solid electrolyte layer, and the composite pole piece including a substrate layer, a metal layer, a lithium-philic layer and a solid electrolyte layer, the thickness of the metal layer may be the same or different. Exemplarily, the thickness of the metal layer may be 0.5 μm to 5 μm; as an example, the thickness of the metal layer may be any point value among 0.5 μm, 0.6 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or a range value between any two of them.

[0071] By limiting the thickness of the substrate layer and the metal layer, the metal layer and the polymer layer can be more tightly bonded, with higher tensile strength and elongation, while minimizing the weight of the current collector and improving the energy density of the battery.

[0072] In the two composite pole pieces provided above, that is, the composite pole piece including a substrate layer, a metal layer and a solid electrolyte layer, and the composite pole piece including a substrate layer, a metal layer, a lithium-philic layer and a solid electrolyte layer, the thickness of the solid electrolyte layer can be the same. For example, the thickness of the solid electrolyte layer is 0.1mm to 3mm; as an example, the thickness of the solid electrolyte layer can be any point value of 0.1μm, 0.2μm, 0.5μm, 1μm, 1.5μm, 2μm, 3μm or any range value between two of them. By making the thickness of the solid electrolyte layer within the above range, the battery can have sufficient mechanical strength and meet the requirements of battery energy density. If the thickness of the solid electrolyte layer is too small, the mechanical strength is low and it is easy to break. If the thickness of the solid electrolyte layer is too large, the energy density is affected.

[0073] In an embodiment of the present application, the solid electrolyte layer further includes a binder, that is, the solid electrolyte layer includes a second solid electrolyte and a binder. Among them, the binder can be a binder conventionally used in solid electrolyte membranes in the art. As an example, optionally, in the solid electrolyte layer, the binder includes, but is not limited to, one or more of polyvinyl alcohol (PVA), polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, styrene-butadiene rubber, nitrile rubber, polyamide, polyethyleneimine or polyimide. Preferably, the binder is selected from PVA.

[0074] However, the present application is not limited to these binders, and other traditional materials or improved materials that can be used as binders in batteries can also be used in the present application. The above-mentioned binders can be used alone or in combination of two or more.

[0075] Optionally, in the solid electrolyte layer, the mass ratio of the binder to the solid electrolyte is (0.5-5):(95-99.5). For example, the mass ratio of the binder to the solid electrolyte can be 0.5:99.5, 1:99, 2:98, 3:97, 4:95, 5:95, etc.

[0076] In some embodiments, the positive electrode sheet further includes a current collector, and the active material layer is disposed on at least one side surface of the current collector along the thickness direction. That is, the positive electrode sheet includes a current collector and an active material layer disposed on at least one side surface of the current collector along the thickness direction.

[0077] The above-mentioned "active material layer disposed on at least one side surface of the current collector along the thickness direction" means that the active material layer can be disposed on one surface of the current collector along its own thickness direction, or on two surfaces of the current collector along its own thickness direction. The "surface" here can be the entire area of ​​the current collector, or it can be a partial area of ​​the current collector. For example, in this embodiment, the surface can be a partial area of ​​the current collector. This application has no special restrictions on this, as long as the purpose of this application can be achieved.

[0078] As an example, the current collector has two surfaces opposite to each other in its thickness direction, and the active material layer is disposed on one surface of the current collector. It is understood that in other embodiments, the active material layer can also be stacked on the two surfaces of the current collector.

[0079] In the embodiment of the present application, the material of the current collector in the positive electrode sheet is not specifically limited. As an example, the current collector can be aluminum, nickel, copper, stainless steel, iron, titanium or carbon, etc., and the shape is foil or mesh; or the current collector can also be a composite current collector including a polymer substrate layer, etc.

[0080] In the embodiment of the present application, the active material layer further includes a positive electrode active material, a conductive agent and a binder, that is, the active material layer includes a positive electrode active material, a conductive agent, a binder and a first solid electrolyte.

[0081] Optionally, in the active material layer, the mass ratio of the positive electrode active material, the first solid electrolyte, the conductive agent and the binder is (70-80): (15-28): (0-4): (0.5-2); wherein the content of the conductive agent preferably does not include 0. As an example, the mass ratio of the positive electrode active material, the first solid electrolyte, the conductive agent and the binder can be 70:28:0.5:2, 75:20:1:1, 80:16:4:2, 80:15:3:1.7, etc.

[0082] It is understood that the mass ratio of the positive electrode active material, the first solid electrolyte, the conductive agent and the binder is related to the electrical performance of the corresponding battery. By controlling the ratio of each substance in the active material layer within the above range, the role of the positive electrode active material, the first solid electrolyte and other materials in combination can be fully utilized, and the cycle performance of the positive electrode sheet can be effectively improved.

[0083] In some embodiments, the positive electrode active material includes, but is not limited to, lithium cobalt oxide (LiCoO 2 )、LiNiO 2 ), lithium manganese oxide (LiMnO 2), any one of lithium cobalt nickel oxide, lithium cobalt manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (ternary material NCM) or lithium nickel cobalt aluminum oxide (ternary material NCA) or a combination of at least two of them. For the sake of brevity, the combinations within the above range are no longer listed one by one.

[0084] For example, the positive electrode active material can be a ternary material NCM, LiMnO 2 Or one or more of lithium nickel manganese oxide.

[0085] However, the present application is not limited to these positive electrode active materials, and other traditional materials or improved positive electrode active materials that can be used as positive electrode active materials for batteries can also be used in the present application. The above-mentioned positive electrode active materials can be used alone or in combination of two or more.

[0086] In the embodiment of the present application, in the active material layer, the conductive agent can use any conductive material as the conductive material as long as it does not cause chemical changes. For example, the conductive agent can be selected from one or more of graphite, conductive carbon black, carbon nanotubes, and carbon fibers.

[0087] In the embodiment of the present application, in the active material layer, the binder may include various adhesive polymers, for example, the binder may be selected from one or more of polyvinyl hexanoate, polyvinylidene fluoride, polypropylene alcohol, sodium carboxymethyl cellulose, polyacrylic acid or nano-silica gel.

[0088] In the examples of the present application, a solvent is also used when preparing the active material layer, and the solvent includes but is not limited to at least one of N-methylpyrrolidone, toluene, butyl butyrate or anisole.

[0089] In an embodiment of the present application, in the positive electrode sheet, the thickness of the active material layer is 30μm to 140μm; further, it can also be 60μm to 110μm; as an example, the thickness of the active material layer can be 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 140μm, etc.

[0090] It should be understood that the coating thickness of the active material layer is related to the battery capacity. The thicker the active material layer, the greater the battery capacity. However, since the coating thickness is related to the charging rate, if the thickness is greater, the lithium ion transmission rate will be reduced while ensuring the battery capacity, and the charging rate will be correspondingly slowed down. Therefore, it is necessary to ensure the battery capacity and charging rate and control the thickness of the active material layer within the above range of 30μm to 140μm.

[0091] Thus, based on the above scheme, an electrode assembly is provided. First, the electrode assembly can be used to prepare a solid-state battery, and the composite electrode sheet in the electrode assembly can form a non-negative electrode lithium battery without conventional negative electrode material coating, which can reduce the weight of the electrode assembly and improve the energy density; and there is no liquid electrolyte inside the non-negative electrode lithium battery, which can avoid the problem of continuous side reactions between lithium metal and electrolyte, and can simultaneously improve the energy density and cycle performance of the battery. Secondly, the positive electrode sheet in the electrode assembly includes an active material layer, and the active material layer includes a first solid electrolyte. The composite electrode sheet is provided with a solid electrolyte layer on one side close to the positive electrode sheet, which can enable lithium ions to be conducted in the positive electrode and the composite electrode sheet, which is conducive to improving the ion conductivity; and the second solid electrolyte in the solid electrolyte layer on the side of the composite electrode sheet has a lithium potential of ≤ the lithium potential of the first solid electrolyte in the positive electrode sheet, so that the voltage platform of the whole battery is high, and the energy density of the battery can be improved accordingly, and it has a higher ion conductivity. Thirdly, the composite electrode sheet in the electrode assembly uses a substrate layer to replace part of the metal, which greatly reduces the weight of the fluid, thereby improving the energy density of the battery. Moreover, when the battery is short-circuited, since the substrate layer is a polymer material, the polymer material melts after being heated, the current collector breaks, and the current is blocked, thereby effectively reducing the probability of thermal runaway of the battery. On the other hand, the battery composed of composite pole pieces does not have liquid electrolyte, is not easy to burn, and can also effectively reduce the probability of thermal runaway. Furthermore, the composite pole piece in the electrode assembly can also adopt a solution combining a lithium-philic layer and a solid electrolyte layer, which can induce uniform electrochemical deposition of lithium ions, thereby effectively inhibiting lithium dendrites.

[0092] Based on the same inventive concept, the present application also provides a method for preparing an electrode assembly, the method comprising: forming an active material layer on at least one side surface of the current collector to obtain a positive electrode sheet; forming a metal layer on at least one side of the substrate layer, and forming a solid electrolyte layer on the surface of the metal layer to obtain a composite electrode; Alternatively, a metal layer is formed on at least one side of the substrate layer, a lithium-philic layer is formed on the surface of the metal layer, and a solid electrolyte layer is formed on the surface of the lithium-philic layer to obtain a composite electrode; The positive electrode sheet and the composite electrode sheet are combined to obtain the electrode assembly.

[0093] During the preparation of the electrode assembly of this embodiment, the positive electrode sheet and the composite electrode sheet may be prepared separately first, and then the prepared positive electrode sheet and the composite electrode sheet may be compounded to obtain an electrode assembly, wherein the active material layer of the positive electrode sheet needs to be arranged in contact with the solid electrolyte layer of the composite electrode sheet.

[0094] Optionally, in the embodiment of the present application, when preparing the positive electrode sheet, the raw materials in the active material layer are first mixed with the solvent in proportion, such as dissolving the positive electrode active material, the first solid electrolyte, the conductive agent and the binder in the solvent (such as the solvent can be at least one of N-methylpyrrolidone, toluene, butyl butyrate or anisole), mixing evenly to obtain a slurry, coating the slurry on the current collector, and obtaining the positive electrode sheet after drying and other processes. The solid content of the slurry can be 40% to 80%.

[0095] By making the solid content of the slurry within the above-mentioned range of 40% to 80%, the uniformity of the slurry can be improved, and the coating surface density and coating quality can be guaranteed. If the solid content of the slurry is too low, the slurry is prone to precipitation, solid-liquid stratification, and a relatively large tail will appear during coating, affecting the coating surface density and appearance; if the solid content of the slurry is too high, the slurry viscosity is high, the powder is difficult to disperse, and the slurry fluidity is low, which also affects the surface density.

[0096] Optionally, in some embodiments, when preparing the composite electrode, a metal layer is first formed on at least one side of the substrate layer, and then a solid electrolyte layer is formed on the surface of the metal layer to obtain the composite electrode. The material of the metal layer includes a metal material with lithium affinity.

[0097] Optionally, in some other embodiments, a metal layer is first formed on at least one side of the substrate layer, and then a lithium-philic layer is formed on the surface of the metal layer, and then a solid electrolyte layer is formed on the surface of the lithium-philic layer to obtain a composite electrode.

[0098] In the preparation methods of the above two composite pole pieces, the metal layer is formed by methods including, but not limited to, at least one of physical vapor deposition, mechanical pressing, chemical plating or gravure coating, wherein the physical vapor deposition method can be at least one of magnetron sputtering, crucible boat evaporation coating or electron beam evaporation coating.

[0099] The metal layer can be formed by the above-mentioned deposition, mechanical pressing, chemical plating and other methods. The specific operation mode or conditions are known to those skilled in the art and are not limited thereto.

[0100] In the embodiment of the present application, the formation method of the lithium-philic layer includes but is not limited to immersion, coating, etc. As an example, when the material of the lithium-philic layer is graphene, a reduced graphene oxide dispersion can be prepared first, and then the prepared electrode including the substrate layer and the metal layer is placed in the reduced graphene oxide dispersion, and after high-temperature drying, a lithium-philic layer can be formed on the surface of the metal layer.

[0101] In the embodiment of the present application, the formation method of the solid electrolyte layer on the metal layer or the lithium-philic layer includes but is not limited to dry film formation or wet film formation. For example, a material containing a second solid electrolyte and a binder can be coated on the metal layer or the lithium-philic layer to form a solid electrolyte layer; or a solid electrolyte layer (film) can be prepared by dry film formation, and then the prepared solid electrolyte layer is compounded with the metal layer or the lithium-philic layer to obtain a composite electrode.

[0102] In the embodiments of the present application, the second solid electrolyte in the solid electrolyte layer can be prepared by various methods well known in the art. As an example, the method for obtaining the second solid electrolyte includes but is not limited to a solid phase method, a sol-gel method, a hydrothermal synthesis method or a melt cooling method. The present application does not limit the specific preparation method of the solid electrolyte.

[0103] It should be understood that the “method for preparing the electrode assembly” and the aforementioned “electrode assembly” are based on the same inventive concept, and all the features and advantages described above for the “electrode assembly” are also applicable to the “method for preparing the electrode assembly” and will not be repeated here one by one.

[0104] In some embodiments, a solid-state battery is provided, comprising: the aforementioned electrode assembly or the electrode assembly prepared by the aforementioned preparation method.

[0105] In the embodiment of the present application, the solid-state battery is an all-solid-state battery, and the solid-state battery can be a negative electrode-free lithium battery, that is, a negative electrode-free all-solid-state lithium battery.

[0106] Since the solid-state battery uses the electrode assembly of this embodiment, it can induce uniform electrochemical deposition of lithium ions, thereby effectively suppressing lithium dendrites, and has a high energy density and excellent cycle performance, as well as a low thermal runaway rate.

[0107] Optionally, the solid-state battery includes the provided electrode assembly. In addition, the solid-state battery may also include other structures known in the art such as a shell, which is not limited to this.

[0108] Example Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this area or the product instructions are used. If the manufacturer of the reagents, materials or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0109] Example 1 (1) Preparation of composite electrode A composite pole piece, such as Figure 1As shown, it includes a stacked substrate layer 1, a metal layer 2, a lithium-philic layer (graphene layer) 3 and a solid electrolyte layer 4; the metal layer 2 is located on both side surfaces of the substrate layer 1; the graphene layer 3 is located on the surface of the metal layer 2, and the solid electrolyte layer 4 is located on the surface of the graphene layer 3.

[0110] The material of the substrate layer 1 is polypropylene with a thickness of 5 μm, and the material of the metal layer 2 is copper, which is deposited on both sides of the polymer substrate layer by evaporation, and the thickness of the metal layer 2 on one side is 1 μm.

[0111] The electrode of the substrate layer 1 with the metal layer 2 deposited thereon is immersed in a 2 mg / mL reduced graphene oxide dispersion for 4 hours, and then dried at 60°C to obtain a graphene layer with a single-side thickness of 2 μm, that is, a lithium-philic layer 3 is formed on the surface of the metal layer 2.

[0112] The second solid electrolyte in the solid electrolyte layer 4 is a NASICON structure LATP electrolyte, and the thickness of the single-side solid electrolyte layer 4 is 1.5 mm.

[0113] The specific preparation method of the solid electrolyte layer is as follows: S1: weigh 152.6g Li and 2 CO 3 、30.6g Al 2 O 3 , 271.5g TiO 2 、610g NH 4 H 2 (PO 4 ) 3 The raw materials were placed in a ball mill together with 220 mL of isopropanol and ball milled for 6 h to obtain a raw material slurry; S2: then put the above raw material slurry into a 60°C oven and dry it for 12 hours, then put the dried powder into a muffle furnace and calcine it at 880°C in air for 3 hours to obtain powder; S3: Then the powder from step S2 and 3.84 g of Li 3 PO 4 Place in the spherical ink tank for 5 hours; S4: then calcining the mixed powder obtained in step S3 at 850° C. in air for 6 h to obtain NASICON structure LATP electrolyte powder; S5: Then, a small amount of PVA binder (the mass ratio of NASICON structure LATP electrolyte powder to PVA binder is 99.5:0.5) is added to the NASICON structure LATP electrolyte powder obtained in S4 and a thin sheet with a thickness of 1.5 mm is made at 200 MPa to obtain a NASICON structure LATP electrolyte layer, that is, a solid electrolyte layer.

[0114] The obtained solid electrolyte layer is composited on the above lithium-philic layer by calendering to obtain a composite electrode.

[0115] (2) Preparation of positive electrode The ternary material LiNi 0.8 Co 0.1 Mn 0.1 O 2 , NASICON structure LATP electrolyte (the first solid electrolyte), conductive carbon black, and polyvinylidene fluoride are mixed in a mass ratio of 71.5:25:2:1.5, and the solvent is anisole to obtain a slurry with a solid content of 75%, which is then coated on the current collector and dried to obtain a positive electrode sheet.

[0116] (3) Preparation of solid-state batteries Then the composite electrode and the positive electrode are assembled into a negative electrode-free lithium battery, and the solid electrolyte layer in the composite electrode is in contact with the active material layer in the positive electrode. The first solid electrolyte in the positive electrode and the second solid electrolyte in the composite electrode are both NASICON structure LATP electrolytes, and the voltage window of the NASICON structure LATP electrolyte is 2 to 5V.

[0117] Example 2 The difference between Example 2 and Example 1 is that the first solid electrolyte in the positive electrode sheet is a perovskite-type LLTO electrolyte (which can be synthesized by a solid phase method); the voltage window of the perovskite-type LLTO electrolyte is 1.5 to 4V; the second solid electrolyte in the composite electrode solid electrolyte layer is a garnet-type LLZO electrolyte (which can be synthesized by a solid phase method); the voltage window of the garnet-type LLZO electrolyte is 0 to 3V.

[0118] The rest are the same as in Example 1.

[0119] Example 3 The difference between Example 3 and Example 1 is that the second solid electrolyte in the composite electrode solid electrolyte layer is a perovskite-type LLTO electrolyte; the voltage window of the perovskite-type LLTO electrolyte is 1.5 to 4V.

[0120] The rest are the same as in Example 1.

[0121] Example 4 The difference between Example 4 and Example 1 is that the second solid electrolyte in the composite electrode solid electrolyte layer is a garnet-type structure LLZO electrolyte (which can be synthesized by a solid phase method); the voltage window of the garnet-type structure LLZO electrolyte is 0 to 3V.

[0122] The rest are the same as in Example 1.

[0123] Example 5 The difference between Example 5 and Example 1 is that the lithium-philic layer is a tin oxide layer; The rest are the same as in Example 1.

[0124] Example 6 The difference between Example 6 and Example 1 is that the material of the metal layer is silver and does not contain a lithium-philic layer; The rest are the same as in Example 1.

[0125] Example 7 The difference between Example 7 and Example 1 is that the material of the substrate layer is polyethylene terephthalate; The rest are the same as in Example 1.

[0126] Example 8 The difference between Example 8 and Example 1 is that the thickness of the substrate layer is 3 μm, the thickness of the single-sided metal layer is 0.5 μm, the thickness of the single-sided lithium-philic layer is 1 μm, and the thickness of the single-sided solid electrolyte is 0.5 mm; The rest are the same as in Example 1.

[0127] Example 9 The difference between Example 9 and Example 1 is that the thickness of the substrate layer is 10 μm, the thickness of the single-sided metal layer is 3 μm, the thickness of the single-sided lithium-philic layer is 5 μm, and the thickness of the single-sided solid electrolyte is 3 mm; The rest are the same as in Example 1.

[0128] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that copper foil is used to replace the substrate layer, the metal layer and the lithium-philic layer in Example 1; That is, in Comparative Example 1, the composite electrode comprises a copper foil and a solid electrolyte layer disposed on the copper foil; The rest are the same as in Example 1.

[0129] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the lithium-philic layer in Example 1 is not contained; The rest are the same as in Example 1.

[0130] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the voltage window of the first solid electrolyte in the positive electrode sheet is smaller than the voltage window of the second solid electrolyte in the composite electrode sheet; Among them, the voltage window of the first solid electrolyte in the positive electrode sheet is 0 to 3V, and the voltage window of the second solid electrolyte in the composite electrode sheet is 2 to 5V; The rest are the same as in Example 1.

[0131] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the first solid electrolyte is omitted in the active material layer of the positive electrode sheet; The rest are the same as in Example 1.

[0132] Performance Testing The above examples and comparative examples were tested according to the following test conditions: (1) First efficiency test: After the battery is manufactured, it is first charged to 3.75V at a constant current of 0.1C to obtain the formation capacity C0. Then the battery is divided into different capacities, charged to 4.2V at a constant current of 0.33C, and then charged to I≤0.05C at a constant voltage of 4.2V to obtain the battery capacity C1 after the capacity division. After standing for 5 minutes, the battery is discharged to 2.8V at a constant current of 1C to obtain the discharge capacity C2, and then discharged to 2.8V at a constant current of 0.1C to obtain the discharge capacity C3, and then discharged to 2.8V at a constant current of 0.01C to obtain the discharge capacity C4; the first coulomb efficiency (first efficiency) is calculated as (C2+C3+C4) / (C0+C1)*100%.

[0133] (2) Capacity retention rate test: at 25°C, the prepared battery was charged at a rate of 0.33C and discharged at a rate of 0.33C, and the discharge capacity was recorded as the discharge capacity of the first cycle. The battery was allowed to stand for 10 minutes and then cycled to record the discharge capacity of the battery at the 100th cycle.

[0134] The capacity retention rate of the 100th cycle = the discharge capacity of the 100th cycle / the discharge capacity of the 1st cycle * 100%.

[0135] (3) Energy density: The battery was placed in a 25°C environment for 30 minutes, charged to 4.25V at 0.5C constant current, then charged to 0.05C at constant voltage, placed for 30 minutes, and discharged to 2.5V at 1C. The discharge capacity and discharge voltage data were collected. Then, 1C energy density = 1C discharge capacity * 1C discharge average voltage / total weight of the battery.

[0136] The test results are shown in Table 1.

[0137] Table 1 Performance test results of various embodiments and comparative examples As can be seen from Table 1, by comparing Examples 1 to 9 with Comparative Examples 1 to 4, it can be seen that the battery made using the electrode assembly provided by the embodiment of the present invention has improved the first effect, cycle performance and energy density to a certain extent. This is because the electrode assembly provided by the embodiment of the present invention can avoid the problem of continuous side reactions between lithium metal and the electrolyte, thereby improving the cycle performance of the battery. In addition, generally, the first effect will be higher when the ionic conductivity is higher, which can indirectly indicate that the battery made using the electrode assembly provided by the embodiment of the present invention has a higher first effect and therefore also has a higher ionic conductivity.

[0138] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0139] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.

[0140] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0141] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An electrode assembly, characterized in that: The electrode assembly comprises: a positive electrode sheet and a composite electrode sheet; The positive electrode sheet includes an active material layer, and the active material layer includes a first solid electrolyte; The composite pole piece includes a solid electrolyte layer, the solid electrolyte layer is arranged close to the active material layer, the solid electrolyte layer includes a second solid electrolyte, and the voltage window of the second solid electrolyte is less than or equal to the voltage window of the first solid electrolyte.

2. The electrode assembly according to claim 1, characterized in that: The first solid electrolyte includes at least one of a NASICON structure LATP electrolyte, a NASICON structure LAGP electrolyte, or a perovskite structure LLTO electrolyte; And / or, the second solid electrolyte includes at least one of a NASICON structure LATP electrolyte, a NASICON structure LAGP electrolyte, a perovskite structure LLTO electrolyte, a garnet structure LLZO electrolyte, a garnet structure LLZTO electrolyte, LiPON or LISICON.

3. The electrode assembly according to claim 1, characterized in that: The composite pole piece also includes a substrate layer and a metal layer; The metal layer is disposed on at least one side surface of the substrate layer along the thickness direction; The solid electrolyte layer is disposed on a surface of the metal layer away from the substrate layer; Wherein, the material of the metal layer includes a metal material having lithium affinity.

4. The electrode assembly according to claim 3, characterized in that: The metal material having lithium affinity includes at least one of gold, silver, tin, magnesium, antimony, indium or aluminum; And / or, the material of the substrate layer includes a polymer material; the polymer material includes at least one of polyamide, polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyterephthalamide, paraphenylenediamine, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber or polycarbonate.

5. The electrode assembly according to claim 1, characterized in that: The composite pole piece also includes a substrate layer, a metal layer and a lithium-philic layer; The metal layer is disposed on at least one side surface of the substrate layer along the thickness direction; The lithium-philic layer is disposed on a surface of the metal layer away from the substrate layer; The solid electrolyte layer is disposed on a surface of the lithium-philic layer away from the metal layer.

6. The electrode assembly according to claim 5, characterized in that: The material of the metal layer includes at least one of copper, nickel, titanium, chromium, steel, molybdenum or tungsten; And / or, the material of the lithium-philic layer includes at least one of tin oxide, copper oxide, zinc oxide, cobalt oxide, nickel oxide, cuprous sulfide or graphene; And / or, the material of the substrate layer includes a polymer material; the polymer material includes at least one of polyamide, polyethylene terephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, polyterephthalamide, paraphenylenediamine, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber or polycarbonate; And / or, the thickness of the lithium-philic layer is 1 μm to 5 μm.

7. The electrode assembly according to any one of claims 3 to 6, characterized in that: The thickness of the substrate layer is 3 μm to 20 μm; And / or, the thickness of the metal layer is 0.5 μm to 5 μm; And / or, the thickness of the solid electrolyte layer is 0.1 mm to 3 mm; And / or, the solid electrolyte layer further includes a binder.

8. The electrode assembly according to any one of claims 1 to 6, characterized in that: The positive electrode sheet further comprises a current collector, and the active material layer is arranged on at least one side surface of the current collector along the thickness direction; And / or, the active material layer further includes a positive electrode active material, a conductive agent and a binder, and the mass ratio of the positive electrode active material, the first solid electrolyte, the conductive agent and the binder is (70-80): (15-28): (0-4): (0.5-2).

9. The method for preparing an electrode assembly according to any one of claims 1 to 8, characterized in that: The method comprises: forming an active material layer on at least one side surface of the current collector to obtain a positive electrode sheet; forming a metal layer on at least one side of the substrate layer, and forming a solid electrolyte layer on the surface of the metal layer to obtain a composite electrode; Alternatively, a metal layer is formed on at least one side of the substrate layer, a lithium-philic layer is formed on the surface of the metal layer, and a solid electrolyte layer is formed on the surface of the lithium-philic layer to obtain a composite electrode; The positive electrode sheet and the composite electrode sheet are combined to obtain the electrode assembly.

10. A solid-state battery, characterized in that: The solid-state battery comprises: An electrode assembly as claimed in any one of claims 1 to 8 or an electrode assembly made according to the method of claim 9.

Citation Information

Patent Citations

  • Composite structure and preparation method and application thereof

    CN117936922A

  • Solid-state battery and preparation method thereof, and electric vehicle

    CN111370751A

  • Bipolar lithium ion battery and preparation method thereof

    CN112582666A

  • Metal lithium negative electrode, preparation method thereof and secondary battery

    CN116565136A

  • Lithium metal negative electrode and secondary battery

    CN216749962U